(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2017)
The study aims to analyze the social and economic factors affecting the growth of informal trade in the market Israel Lewites of Managua. Is a research descriptive. Among the main causes of the growth of informal trade in market Israel Lewites are lack of regular employment, lack of work experience, marriage and early motherhood, discrimination in the case of women, education is the most important factor, since has been identified that the majority of people failed to finish secondary studies.